2022
DOI: 10.1097/mpg.0000000000003537
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Probiotics in Pediatric Nonalcoholic Fatty Liver Disease: A Meta-analysis of Randomized Control Trials

Abstract: Objectives: We conducted a systematic review and meta-analysis to provide a summary of the current literature about the efficacy of probiotics in pediatric nonalcoholic fatty liver disease (NAFLD). Methods: A systematic literature search through major electronic databases was carried out for RCTs till September 9, 2021, investigating the efficacy of probiotics in the treatment of pediatric patients with NAFLD. Weighted mean differences (WMD) and Standard Deviations (SD) were used to calculate continuous outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The study was limited with small group numbers and a short follow up of 12 weeks. The study showed agreement with earlier studies included in a systematic review (81–83). Overall, there remains a paucity of robust evidence to recommend use of a particular probiotic for the management of MAFLD.…”
Section: Managementsupporting
confidence: 90%
“…The study was limited with small group numbers and a short follow up of 12 weeks. The study showed agreement with earlier studies included in a systematic review (81–83). Overall, there remains a paucity of robust evidence to recommend use of a particular probiotic for the management of MAFLD.…”
Section: Managementsupporting
confidence: 90%
“…These findings are also consistent with a slightly smaller-scale study in which 22 children with NAFLD who received the VSL#3 probiotic (containing four strains of Lactobacillus , three strains of Bifidobacterium , and one strain of Streptococcus ) for four months had improvement in their disease based on liver ultrasound findings compared to children who received a placebo [ 47 ]. Most promisingly, a meta-analysis of these aforementioned studies as well as two other randomized control trials including a total of 238 pediatric patients with NAFLD revealed a significant improvement in liver transaminases, total cholesterol, triglyceride levels, and ultrasound findings suggestive of liver steatosis in patients who received probiotics compared to those who did not [ 48 ]. However, heterogeneous strains were used in these studies, and long-term benefits of these probiotics for pediatric NAFLD, as well as the underlying mechanisms of protection, remain to be further investigated.…”
Section: Interactions Between the Gut Microbiota And Pediatric Hepato...mentioning
confidence: 99%
“…Similarly, omega-3 fatty acid supplementation was not effective in inducing a significant reduction in ALT or improving liver steatosis on ultrasonography[ 73 ]. Some randomized controlled trials indicated that probiotic supplementation might be beneficial in children with NAFLD, but the current evidence does not specify the exact beneficial strain of probiotics, requiring further studies[ 74 ]. Interestingly, the strategy of targeting the lysosome has seemed to encourage a new direction for future NAFLD treatment, e.g.…”
Section: Challenges In Treatmentmentioning
confidence: 99%